Synthesis of Water-Soluble Polyethylene Glycol Fumarates for Biomedical Applications - Tazhbayev, Ye. M.; Kazhmuratova, A.T.; Zhaparova, L.Zh.; Tuleuov, U.B.; Nassikhatuly, Y.; Mitricheva, E.S.; Kwiatkowski, A.L.; Shibaev, A.V. (Eurasian Journal of Chemistry, 2024)
Polyethylene glycol fumarate (PEGF) with controlled structural composition has been obtained for further synthesis of double network cross-linked hydrogels for biomedical applications. The copolymer has been syn-thesized by polycondensation reaction of fumaric acid and polyethylene glycol (PEG-600). Molecular weight of PEGF has been determined by gel permeation chromatography to be approximately 6000 Da with gel per-meation chromatography. The polycondensation of fumaric acid and PEG-600 was studied throughout the re-action process. The structure of the reaction product has been evidenced using FTIR- and 1H NMR-spectroscopy. The quantitative ratios of the amount of –C=C– bonds and –COO groups to –C=O groups in the obtained PEGF have been estimated from IR-spectra for different synthesis time. The time-dependence of molar ratio of double bonds to methyl groups in PEGF has been obtained from corresponding 1H NMR-spectra. FTIR and 1H NMR-spectroscopy, both, demonstrate that after the end of reaction the unsaturated –C=C– double bonds remain in the structure of the macromonomer, that is essential for further preparation of cross-linked hydrogels. The addition of the tightly cross-linked network of polyvinyl alcohol leads to for-mation of highly tough biocompatible material for preparation of the artificial meniscus which can further be used as a solution in the treatment of diseases such as osteoarthritis.
Keywords: polyethylene glycol; polyethylene glycol fumarate; fumaric acid; polyester resin; macromonomer; hydrogels; FTIR- spectroscopy; 1H NMR-spectroscopy